Penciptaan Tari Beyond Terinspirasi oleh Konflik Diri Dengan Pengidap Attention Deficit Hiperactivity Disorder - Rahmania, Finka Nur (TAMUMATRA, 2024)
The work Tari Beyond is a work that originates from the author's empirical experience in dealing with self-conflict when dealing with a sibling who suffers from Attention Deficit Hyperactivity Disorder (ADHD). Conflicts that can give rise to awareness and acceptance that this is a gift from God Almighty. This research answering two questions, namely: (1) The form of the Beyond dance by Finka Nur Rahmania and (2) The process of creating the dance work Beyond by Finka Nur Rahmania. The theory used to identify forms is the theory of Sri Rochana W. in her book entitled Sejarah Tari Gambyong: Seni Rakyat Menuju Istana, which contains expressed forms and physical forms. Meanwhile, to describe the creation process, we use theories from Sri Rochana W. and Dwi Wahyudiarto in a book entitled Pengantar Koreografi which includes exploration, organization, unity, presentation. This research uses interpretive descriptive research methods through qualitative data. This research uses data collection techniques through observation, interviews and literature study. Data from this research was obtained from researchers as authors or participant observers. Beyond's dance work is unique in its form which is based on hip-hop and contemporary dance which expresses awareness and acceptance of situations that do not match expectations.